Magnesium Deficiency Reduced the Yield and Seed Germination in Wax Gourd by Affecting the Carbohydrate Translocation - Zhang, Baige; Cakmak, Ismail; Feng, Jianchun; Yu, Chaoran; Chen, Xiao; Xie, Dasen; Wu, Liangquan; Song, Zhao; Cao, Jian; He, Yuzhi (Frontiers in Plant Science, 2020)
Magnesium (Mg) is a particular mineral nutrient greatly affecting the size and activity of sink organs. Wax gourd crop with its fruits having fresh weight up to 20-50 kg per single fruit serves as an excellent experimental plant species for better understanding the role of varied Mg nutrition in sink strength and yield formation. This study aimed to investigate the effects of Mg deficiency on fruit yield and seed vigour in wax gourd grown under field conditions. Plants were grown under field conditions until maturity with increasing soil Mg applications. At the beginning of fruit formation, leaves were used to analyse concentrations of sucrose, starch and Mg as well as phloem export of sucrose. At maturity, fruit yield was determined and the seeds collected were used in germination studies and starch analysis. Low Mg supply resulted in a significant impairment in fruit fresh yield, which was closely associated with higher accumulation of starch and sucrose in source leaves and lower amount of sucrose in phloem exudate. Seeds obtained from Mg deficiency plants exhibited lower amount of starch and substantial reduction in both germination capacity and seedling establishment when compared to the seeds from the Mg adequate plants. Our study revealed that magnesium deficiency significantly diminished fruit yield of field-grown wax gourd, most probably by limiting the carbohydrate transport from source organs to developing fruit. Ensuring sufficient Mg supply to plant species with high sink size such as wax gourd, during the reproductive growth stage, is a critical factor for achieving higher fruit yield formation and also better vigour of next-generation seeds.